FAKTOR YANG MEMPENGARUHI PASIEN DALAM MEMANFAATKAN LAYANAN AKUPUNTUR DI KLINIK AKUPUNTUR RSUP. DR. SARDJITO YOGYAKARTA - , SUHARSANA, Prof. Dr.dr. Nyoman Kertia, Sp. PD-KR. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Acupuncture services at Dr. Sardjito Hospital begins since the year 2000. Utilization of acupuncture services showed a significant increase since 2010. Increased utilization of services almost simultaneously with the determination of hospital cooperation with PT Askes. This study was conducted with the alleged link between acupuncture service improvement with PT Askes involvement in the financing of acupuncture services in Dr.Sardjito Hospital. In addition, this study wanted to show what factors influence a patient's decision to utilize the services of acupuncture. Method: This study using a quantitative approach with cross-sectional design. Respondents were outpatients at the hospital Dr.Sardjito that utilizes acupuncture services during the period 1 May 2012 to 30 April 2013 with a minimum age of 18 years. The instrument used was a questionnaire adopted from the research utilization of dental clinic in Pasar Ikan Health Center Bengkulu: From the Patient Perspective 2002. This study began in June to August 2013. Data processing use the data analysis was done by using the program Stata 12.0 SE, which is descriptively calculate the frequency distribution of variables, bivariate analysis using chi-square, and multivariate analysis using logistic regression. Result: This study involved 58 respondents, 22 respondents is patient of Askes and 36 is general patient. The respondents patient of Askes complete acupuncture therapy by 68%. While the respondents general patients which has a complete acupuncture therapy by 21%. A total of 23% the respondents stated that groove serpentine services, 23% said the equipment is not complete, and respondents who utilize acupuncture services to avoid the side effects of drugs by 96%. The respondents patient of Askes has a utilization rate of 33 times greater than the respondents of general patient. Conclusion: Patterns of service utilization of acupuncture in acupuncture clinic Dr. Sardjito Hospital of predisposing factors is age and respondents' perceptions of the completeness of the facility, while the enabling factor is health insurance. The most dominant factor affecting the use of acupuncture in hospital services. Dr. Sardjito Hospital is health insurance. Keyword: Utilization, services, acupuncture